The cellular location of self-antigen determines the positive and negative selection of autoreactive B cells. - Ferry, H; Jones, M; Vaux, D; Roberts, I; Cornall, R (2003)
Systemic autoimmune disease is frequently characterized by the production of autoantibodies against widely expressed intracellular self-antigens, whereas B cell tolerance to ubiquitous and highly expressed extracellular antigens is strictly enforced. To test for differences in the B cell response to intracellular and extracellular self-antigens, we sequestered a tolerogenic cell surface antigen intracellularly by addition of a two amino acid endoplasmic reticulum (ER) retention signal. In contrast to cell surface antigen, which causes the deletion of autoreactive B cells, the intracellularly sequestered self-antigen failed to induce B cell tolerance and was instead autoimmunogenic. The intracellular antigen positively selected antigen-binding B cells to differentiate into B1 cells and induced large numbers of IgM autoantibody-secreting plasma cells in a T-independent manner. By analyzing the impact of differences in subcellular distribution independently from other variables, such as B cell receptor affinity, antigen type, or tissue distribution, we have established that intracellular localization of autoantigen predisposes for autoantibody production. These findings help explain why intracellular antigens are targeted in systemic autoimmune diseases.